Improvement in fractional shortening in aortic regurgitation rats: cardiac muscle network - Omoko, Ana Carolina Mieko [UNESP]; Fernandez, Geysson [UNESP]; Moraes, Leonardo Nazario [UNESP]; Roscani, Meliza Goi; Carvalho, Robson Francisco [UNESP]; Gobbi, Juliana Irani Fratucci de [UNESP] (My University, 2015)
Aortic regurgitation (AR), a volume overload to the heart, impairs systolic function. Paroxetine (parox) treatment, a selective serotonin reuptake inhibitor, improves systolic function in AR rats, probably due decreases in the expression of β-myosin heavy chain (βMyHC) gene. An intricate network regulate genes co-expressing microRNAs (miR-208a,-208b and -499) and transcriptional repressors which in turn controls MyHCisoforms content. Thus, we verify the gene expression of those microRNAs and the transcriptional repressor (Thrap1) in AR rats treated with parox. Male Wistar rats (280-300kg) were submitted to sham or AR surgery. Morphofunctional variables of the hearts were analyzed by echocardiograms. Parox (10mg/kg) was administered subcutaneously for 4 weeks. There were 4 groups: AR+parox, AR+saline, Sham+parox and Sham+saline. At week 8 the animals were euthanized for tissue collection and analysis of gene expression by RTq-PCR. Two way repeated measures ANOVA were used for comparisons. Parox treatment preserved the fractional shortening in AR rats. The expression of miR-208a and Thrap 1 were not changed. Though there was a decrease in miR-208b and miR-499 gene expression, which may regulate the decrease of β-MyHC isoform in AR rats treated with parox, explaining the improvement in systolic function.